(Não) vai dar chabu! a festa do fogo no São João de Estância-SE - Silva, Priscila Santos (2011)
The parties provide the exercising of human relations, because they are forms of collective actions symbolic and materially planed, prepared, constructed and executed. They are delimited by time and space and evoke the enchantment through the spectacle and the condemnation to clamor through their normalization. The parties also confer prestige and produce identity by linking themselves around an object. It is possible for the culture to materialize them because they serve not only for utilitarian purpose. As well they develop ludic and esthetics roles. In this thesis the Saints John s festival event in Estância was analyzed under a socio-anthropologic optic. I turned my attention to festa de fogo (activity that involves the presence of fireworks- busca-pé, espada e barco de fogo). This event has been present in Saint John s celebration for more than one hundred years. To its study I revived the city s stories about Saints John s festival and observed the changes that occurred in its celebration. I turned my attention to the conflicts, permanencies and prohibitions occurred through time. It was elected as the analyze method the ethnography from the public presentations and behind scene facts. One of the most important aspects of festa de fogo is the role of cultural artifact represented by the fireworks. They develop important functions inside the festival because they are the link between the process of formation and demarcation of the party and the city s identity. Moreover, they engross the risk caused by the chabu that are controlled by public politics of incentive to culture and tourism. The fireworks are also involved in the prestige given to the fogueteiro - he is a character who suffers the process of modernization according to the city and party s dynamic.